Aplikasi Bioinsektisida Berbasis Jamur Entomopatogen Terhadap Penggerek Batang Padi Daerah Pasang Surut Sumatera Selatan - Khodijah Khodijah (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2014)
Population and the intensity of the rice stem borer attack can influence pesticide application. This study aimed to examine the effect of active ingredient formulation of solid and liquid Beauveria bassiana bioinsecticide to control rice stem borer (PBP). The research was conducted in tidal lowland rice cultivation in the Village Mulya Sari Banyuasin Regency, South Sumatra, from Maret 2012 to Juni 2012. Observations of population and intensity of attacks observed directly on the rice clump clump as many as 80 samples per ha. The results showed that the application of liquid and solid bio insecticide with active entomopathogenic fungi material effected on the population, the intensity of PBP larvae attack. The results showed that the application of liquid and solid bio insecticide with entomopathogenic fungi active material in the tidal land effect on the population, the attack intensity of PBP larvae. The results found that in tidal land application of liquid bio insecticide could suppress the population aged 10-40 dap of PBP approximately 75%, and solid and bio insecticide approximately 37.5%. Application of liquid bioinsecticide could suppress population aged 50-80 dap of PBP approximately about 55%, and solid bioinsecticide could suppress larval populations of PBP approximately 40%. Liquid bioinsecticide applications could reduce attack intensity PBP of rice plants aged at 10-40 dap approximately 81.75% and approximately 55.44% for solid bioinsecticide. At age 50-80 dap rice, liquid bio insecticide could reduce attack intensity of PBP about 70%, and applications of solid bioinsecticide approximately 60%.